(untitled) - Joyner, Amy (Hoboken, N.J., 2007)
In The Online Millionaire, author and Internet business expert Amy Joyner shows you how to build your own multi-channel online marketing empire, regardless of what products or services you sell. This book introduces you to the most popular Web-based marketplaces and reveals the tricks of the trade for excelling in each one. You'll learn the ins and outs of thriving on eBay, Amazon.com, Yahoo!, Overstock.com, and many others. Plus, you'll discover how to use search engines and comparison-shopping sites to attract customers and drive sales—often at little or no cost. You'll also get the inside scoop on how to build your own professional e-commerce store, along with proven ways to make money promoting related companies and products on your site.
Keywords: Electronic commerce,Internet marketing,Success in business,Thương mại điện tử,Tiếp thị Internet,Thành công trong kinh doanh